2(-5)+7(-25)-9(-5)+21(-50)+5(-5)=

Simple and best practice solution for 2(-5)+7(-25)-9(-5)+21(-50)+5(-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-5)+7(-25)-9(-5)+21(-50)+5(-5)= equation:


Simplifying
2(-5) + 7(-25) + -9(-5) + 21(-50) + 5(-5) = 0

Multiply 2 * -5
-10 + 7(-25) + -9(-5) + 21(-50) + 5(-5) = 0

Multiply 7 * -25
-10 + -175 + -9(-5) + 21(-50) + 5(-5) = 0

Multiply -9 * -5
-10 + -175 + 45 + 21(-50) + 5(-5) = 0

Multiply 21 * -50
-10 + -175 + 45 + -1050 + 5(-5) = 0

Multiply 5 * -5
-10 + -175 + 45 + -1050 + -25 = 0

Combine like terms: -10 + -175 = -185
-185 + 45 + -1050 + -25 = 0

Combine like terms: -185 + 45 = -140
-140 + -1050 + -25 = 0

Combine like terms: -140 + -1050 = -1190
-1190 + -25 = 0

Combine like terms: -1190 + -25 = -1215
-1215 = 0

Solving
-1215 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (k+1)x^2+(k+1)y^2+2kx+2ky+2y+4k+3=0 | | .25x-5+171=x | | 20/12=50/x | | 3(-5)(2)+6(-5)+-5(3(2)-6)= | | 2x+3x+(2+6)=8 | | 7x-2=4x-2 | | y=-2x+16x-24 | | ln(5x-2)-ln(x+3)=2 | | 5(2+p)=17.5 | | 5x+45-89=-90+41 | | 3+2p=7 | | -5(2(2)+7)+2(9)+5(-5)= | | 5(z-1)-20=0 | | Y=2ln(3x-1)-2 | | -10x^2-6x-12=0 | | -4=-8x+2 | | 9(4(-25)-3)= | | ln(x-6)=24 | | 90t=450t | | 9t^2-54=0 | | -24r+6= | | 9(-5)(2)+3(-25)-7(4)+8(-5)(2)-12= | | Y=-8sin(7x) | | 8=2d-12 | | -7x-y+z=-12 | | x-9=.75x | | (5x+5)+(-6x+8)= | | x^2+y^2+18x+12y=11 | | 8b+3=5b+7 | | 3(3x-7)=81(12x-3x) | | 2/12= | | e^7x=10 |

Equations solver categories